PENGARUH FAKTOR INTERNAL KLIEN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK UPGRADE, DOWNGRADE DAN SAMEGRADE - Pratama, Aditya; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
The aim of research to determine effect the client’s internal factor, such as; firm size, financial distress and management changes to switching of public accounting firm (PAF). The population in this study is a company of the banking sector in the Indonesia Stock Exchange the period 2009 to 2014. Sampling was used in this research is purposive sampling and obtained samples of 138 observations. The test used multinomial logistic regression, because there are three categories of the dependent variable. The results of analysis firm size variable negative effect on turnover and samegrade upgrade PAF, PAF while the downgrade does not affect turnover. Financial distress variable do not affected the change of upgrade, downgrade and samegrade. Management changes variable did not affected the change of PAF upgrade, downgrade and samegrade.
Keywords: firm size, financial distress, management changes, switching of PAF